En la periferia del imperio: provincias tributarias aztecas en la frontera imperial - Berdan, Frances F. (Revista Española de Antropología Americana, 2007)
This article deals with the arrangement of conquered provinces in the Aztec empire. It has become widely recognized that the empire employed contrasting imperial strategies resulting in tributary and strategic provinces, the latter often tending to insulate the former from potentially dangerous frontiers. Therefore, it is somewhat problematical to find several tributary provinces established on the fringes of the empire and even along hostile borderlands. Explanations for these arrangements are presented from an examination of historical, economic, and military/administrative dimensions of Aztec empire-building.